PREVALENCE, CLINICAL FEATURES, AND PROGNOSIS OF THE PSYCHOSOMATIC PATHOLOGY IN CHILDREN WITH PSYCHOPHYSICAL DEVELOPMENTAL DISORDERS - Beketova, G.V.; Mozgova, G.P.; Soldatova, O.V.; Nekhaienko, M.I.; Horiacheva, I.P.; Alekseienko, N.V.; Kvashnina, L.V.; Beketova, N.V. (World of Medicine and Biology, 2020)
The article presents the results of the clinical and epidemiological study on the prevalence of psychosomatic pathology (PSP) in Ukraine in children with psychophysical developmental disorders (PPDD). It was found that the prevalence of PSP in children with PPDD did not significantly differ from that in patients without PPDD and was estimated 89 and 86 children per 1000 of child population, respectively. The predominant psychosomatic diseases in children with and without PPDD were bronchial asthma (BA) and duodenal ulcer (DU). In patients with PPDD, the highest prevalence of duodenal ulcer (56%), and bronchial asthma (26%) was observed, while on the contrary in children without PPDD the prevalence of duodenal ulcer was estimated 12% and of bronchial asthma 68%. In children with PSP and PPDD, earlier onset of duodenal ulcer was revealed, as compared to children without PPDD (10.5±0.7 years and 14.2±0.5, respectively). Clinical features of the course of duodenal ulcer in children without PPDD were the prevalence of minor and asymptomatic forms (29.0%) with detection of the first clinical signs of the disease in the form of complications (gastrointestinal bleeding, scar-and-ulcer deformity of duodenum) (8.1%). The same pattern was observed in children with PPDD, however, the frequency of complications in them was significantly higher (14.7%) with longer duration (73.0%) and severity (53.8%) of the disease, as compared to 46.6% and 16.7% in patients without PPDD. Pivotal complex psychological markers of the development of PSP in children with and without PPDD were high levels of personal and reactive anxiety, emotional lability and deviation from autogenous norm, low indicators of self-esteem and poor performance, which required differentiated medical and psychological support.
Keywords: psychosomatic pathology; psychophysical disorders; children; adolescents; risk factors